The many faces of George Washington : remaking a presidential icon - McClafferty, Carla Killough, 1958- (Minneapolis, MN : Carolrhoda Books, 2011)
Veteran children's author McClafferty takes a look at the life of George Washington by chronicling the fascinating process of creating life-sized statues of Washington using the latest modeling techniques.
Includes bibliographical references (p. 117) and index.
Keywords: Washington, George, -- 1732-1799 -- Statues -- Juvenile literature; Washington, George, -- 1732-1799 -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; Famous Persons -- Biography; Famous Persons -- Juvenile Literature